Creating Props: Improving Writing Skills of Teaching Materials of Elementary Teacher Education Students through Project-Based Learning Model - Wardani, Duhita Savira; Fauzi, Muhammad Rizal; Zafira, Ruwaida; Kurniawati, Dian (Mimbar Sekolah Dasar, 2020)
This study aimed to determine the improvement in writing skills of science teaching materials for elementary school teachers students through the Project-Based Learning (PjBL) model. This study used a quasi-experimental method with One Group Pretest-Posttest Design using portfolio assessment sheets to write science teaching materials. Data were analyzed using a T-test. This study's subjects were pre-service teacher students who contracted Natural Science Learning courses in the Elementary Teacher Education Program. The study results indicated that PjBL could increase pre-service teachers' skills in developing teaching materials relevant to the 21st-century skills, students' character, and the applicable curriculum. This result is evidenced by the results of the assessment, which increased significantly from 2.04 to 3.25. It is also based on the Wilcoxon test that Asymp.Sig. (2-tailed) 0.05 which is 0.000. It means that there is an influence in the form of an increase in the PjBL model's use of the writing skills of science teaching materials for elementary teacher students. This study recommends that the PjBL model can be used as an alternative learning model to improve the writing skills of teaching materials for students.